1986
DOI: 10.3168/jds.s0022-0302(86)80499-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Fiber and Physical Form on Performance of Lactating Dairy Cows

Abstract: Two trials were conducted to study the effects of forage intake and physical form on lactating cow performance. In trial 1, four cows in a 4 X 4 Latin square were fed long alfalfa hay at 28, 36, 45, and 53% of total dry matter plus concentrate. Total dry matter intake was not affected by forage percent. Total chewing time and milk fat percentage increased linearly with increasing forage consumption. Maximum 4% fat-corrected milk production occurred when diets contained 27% neutral detergent fiber and 18% acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
11

Year Published

1989
1989
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 25 publications
5
38
1
11
Order By: Relevance
“…Thus, when expressed per unit of NDF intake, the higher level of NDF intake of cows fed the bromegrass diet resulted in a shorter length of time spent eating, ruminating and total length of time eating and ruminating (Table 4). This result agrees with our pervious finding (Okine et al 1994) that dairy cattle in early lactation may maintain a constant rumination time per unit of NDF intake at NDF concentrations greater than the maximum 30% suggested by Woodford et al (1986). The results also suggest that there may be a maximum amount of time that cows irrespective of stage of lactation will chew (Welch and Smith 1970;Okine et al 1994).…”
Section: Chewing Activitiessupporting
confidence: 83%
“…Thus, when expressed per unit of NDF intake, the higher level of NDF intake of cows fed the bromegrass diet resulted in a shorter length of time spent eating, ruminating and total length of time eating and ruminating (Table 4). This result agrees with our pervious finding (Okine et al 1994) that dairy cattle in early lactation may maintain a constant rumination time per unit of NDF intake at NDF concentrations greater than the maximum 30% suggested by Woodford et al (1986). The results also suggest that there may be a maximum amount of time that cows irrespective of stage of lactation will chew (Welch and Smith 1970;Okine et al 1994).…”
Section: Chewing Activitiessupporting
confidence: 83%
“…In addition, Woodford et al (1986) indicated that normal rumen function is dependent on both qualitative (physical form) and quantitative (dietary concentration) aspects of dietary fiber. If the "effectiveness" of dietary fiber in reducing acidosis depends solely on the amount of NDF provided by the forage, then high-concentrate finishing diets containing equal levels of NDF from different forage sources should elicit similar responses in animal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in voluntary intake may relate, in part, to the chewing required for comminution, since grinding and pelleting forages before feeding minimizes intake differences (Heaney et al 1963). were fistulated in the rumen and esophagus (Stevens et al 1985) Chewing Activities Chewing activities were monitored during each period using a strain gauge transducer linked to a computerized data acquisition system as described previously by Beauchemin et al (1989) (Beauchemin 1991;Woodford et al 1986 For personal use only. vS, main effect of forage species; M, main effect of forage maturity; S x M, interaction between species and maturity of forage.…”
mentioning
confidence: 99%